Synthesis, molecular modeling, in vivo study and anticancer activity against prostate cancer of (thorn) (S)-naproxen derivatives - KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2020)
In this study, (S)-naproxen thiosemicarbazides (3a-d), 1,2,4-triazoles (4a-c), triazole-thioether hybride compounds (5a-p) were synthesized and their structures (3a, 3d, 4a and 5a-p) were confirmed by FT-IR, H-1 NMR,C-13 NMR, HR-Mass spectra and elemental analysis. These compounds are designed to inhibit methionine amino peptidase-2 (MetAP2) enzyme in prostate cancer. These compounds (3d, 5a-p) evaluated against androgen-independent prostate adenocarcinoma (PC-3, DU-145) and androgen-dependent prostate adenocarcinoma (LNCaP) cell lines by using MTS method. Compounds 5a, 5b, 5d and 5e showed 14.2, 5.8, 10.8 and 8.4 mM anticancer activity against PC-3 cell lines, compounds 5e, 5g and 5n presented anticancer activity against DU-145 cell lines 18.8, 12.25 and 10.2 mu M, and compounds 5g, 5m and 5n exhibited anticancer activity against LNCaP cell lines 12.25, 22.76 and 2.21 mu M, respectively. Consequently, of these results, compounds 5e and 5n showed the highest activities against androgen dependent and independent prostate cancer cell lines, so these compounds could be potent small molecules against prostate cancer. Furthermore, mitogen-activated protein kinase (MAPK) pathway activation, AKT (protein kinase B) phosphorylation and androgen receptor activation of compound 5n (SGK636) were investigated in LNCaP cells by using Western blot method. Compound 5n (SGK636) was also tested against mRNA expression analysis of the Bax, Bcl-2, Caspase 3, Caspase 9 by using real-time PCR analysis. Compound 5n was given to nude male mice with cancer in comparison to the control group. Compound 5n was found to reverse the malignant phenotype in the nude male mice, whereas the prostate cancer progressed in the control group. Analysis of some blood parameters in the study showed that they were within the normal values with respect to the control. The blood values of the animals treated according to the control group also exhibited compliance with the blood limit values. Molecular docking and dynamics simulation of compound 5n binding toMethionine Aminopeptidase 2 (MetAP2) enzyme rationalized its potential activity. In addition, inhibition assay MetAP2 enzyme of compound 5n was evaluated. Taken together, we suggest compound 5n to be a potential candidate for prostate cancer therapy. (C) 2020 Elsevier Masson SAS. All rights reserved.
Keywords: (S)-naproxen; Methionine aminopeptidase-II; Thioether; Prostate cancer; LNCaP; IVIS; METHIONINE AMINOPEPTIDASE-2; NAPROXEN; INHIBITORS; APOPTOSIS; TRIAL